Business matters : bite-size learning - Kong, Francis J. (Metro Manila, Philippines : Business Matters Publishing, 1998)
There is a great difference between making a living and making a life.
1. On Life --- 2. On Humanity -- 3. On Progress -- 4. On the future -- 5. On Success -- 6. On Happiness -- 7. On Hope -- 8. On Thinking -- 9. On Character -- 10. On Perspective -- 11. On religion -- 12. On Death.
Keywords: QUOTATIONS